O uso de CFD no estudo da dispersão de monóxido de carbono em ambiente urbano - Souza, Délio Barroso de (2016)
The human exposure to Carbon Monoxide (CO) can contribute to emergency episodes due to heart attacks, and even when the exposure time is 50 minutes of order compromises visual acuity. In the urban environment, this exhibition is ongoing, but monitoring concentrations in large spaces is difficult and rarely performed by state officials due to the high cost of operation and maintenance.These concentrations are still affected by the presence of barriers and buildings, by varying traffic conditions, climate conditions ranging over short periods of time. The prediction of the concentration levels of toxic gases and particulate matter, through mathematical models, allows you to establish public health policies considering the effect of many variables that affect the dispersion of air pollutants and adopt prevention and correction of the causative factors. This work proposes the application of mathematical models phenomenological based on the mass of conservative equations, momentum and energy coupled to κ turbulence model - ε, for the simulation of CO dispersion emitted by vehicles in urban environment in the city of Uberlândia (Minas Minas, Brazil), considering downtimes in traffic signals, vehicle type and climatic characteristics of the region and age of the fleet. The computer simulation is performed using the software OpenFOAM®. Dynamic patterns are presented to flow and concentration profiles in a characteristic plot of urban environment 60 meters x 45 meters x 30 meters in size in the presence of a cubic obstacle 5 meters x 5 meters x 5 meters. The CO emission source, distributed in an initial mixing zone, has the estimated load for a given conformation of vehicle queues considered the emissivity at CAL3QHC software. To consider the vehicle downtimes on road signs (73 seconds), the simulations were carried out in two stages. In the first stage, the positioning of the CO source was defined in accordance with the positioning of vehicle queues considering the presence of fresh air throughout the area. The flow structures and CO concentrations in the environment after 73 seconds, defined the background concentration of CO used in whole models. This background concentration can represent a more realistic situation in urban atmosphere and was used to simulate the second stage where new release of CO was simulated by considering the same positioning of the vehicle row of links and the same load distribution. The effect of air speed on the flow patterns and CO concentration distribution was considered values for speeds of 2.34 m/s, 4 m/s and 15 m/s, typical of the studied region. The phenomena of atmospheric stratification, mitigation and heat exchange were adequately provided for in the simulation and demonstrated in what conditions the harmful effects of CO on human health are more acute. They are also presented studies considering the launch of a point source of CO with dimensions of 7 meters x 3 meters x 3 meters, positioned at a 1.80 meters height of the soil to the average height of the population, with and without the presence of the obstacle cúbico.Os results demonstrate the ability of CFD modeling using OpenFOAM associated with the representation of motor vehicles queue links through CAL3QHC algorithm, in representation of the CO dispersion in urban environment.